Improving the accessibility of foundation statistics for undergraduate business and management students using a flipped classroom. Issue 2 (1st February 2021) - Price, Charlotte; Walker, Maria
ABSTRACT: A quantitative study was undertaken to investigate the accessibility of an undergraduate foundation statistics module for business and management students over four consecutive years, before and after the adoption of a flipped classroom teaching approach for a large cohort (∼ 500 students per year). Students' module feedback questionnaires, exam scores, basic student demographics and online engagement and attendance data were analysed. Those taught using the flipped classroom approach found the module significantly more interesting and the proportion of students who perceived the module to be difficult was roughly half that under the traditional teaching approach. However, there was no evidence of a difference in exam performance, class attendance or online engagement under the two teaching approaches. Perceptions of the flipped classroom differed according to gender, nationality and reported prior maths training, but the flipped classroom appears to enhance the student experience by making a traditionally difficult subject feel more accessible.